Viviendas en Palermo - Lanosa-González Ruiz (2004)
Cinco viviendas en Palermo, Buenos Aires, 2000 por el 'Estudio GGR'
Keywords: LANOSA, GABRIEL; GONZÁLEZ RUIZ, JOSU; ARGENTINA; BUENOS AIRES; VIVIENDAS MULTIFAMILIARES; EDIFICIOS DE VIVIENDAS